2022
DOI: 10.1371/journal.pone.0276329
|View full text |Cite
|
Sign up to set email alerts
|

Gastropods underwent a major taxonomic turnover during the end-Triassic marine mass extinction event

Abstract: Based on an exhaustive database of gastropod genera and subgenera during the Triassic–Jurassic transition, origination and extinction percentages and resulting diversity changes are calculated, with a particular focus on the end-Triassic mass extinction event. We show that gastropods suffered a loss of 56% of genera and subgenera during this event, which was higher than the average of marine life (46.8%). Among molluscs, gastropods were more strongly affected than bivalves (43.4%) but less than ammonoids, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…With over 30,000 species, euthyneuran gastropods represent one of the most diverse lineages in Mollusca, and play significant ecological roles in aquatic and terrestrial environments (Ferrari and Hautmann, 2022). The presence of large, identified neurons in representatives of Euthyneura justified the early focus on dopamine signaling with TH-ir or glyoxylate-induced histofluorescence mapping.…”
Section: Discussionmentioning
confidence: 99%
“…With over 30,000 species, euthyneuran gastropods represent one of the most diverse lineages in Mollusca, and play significant ecological roles in aquatic and terrestrial environments (Ferrari and Hautmann, 2022). The presence of large, identified neurons in representatives of Euthyneura justified the early focus on dopamine signaling with TH-ir or glyoxylate-induced histofluorescence mapping.…”
Section: Discussionmentioning
confidence: 99%
“…The Late Triassic Cylindrobullina species from Peru showed the smallest size for the genus at that time, whereas the Pliensbachian Cylindrobullina of southern Patagonia showed the largest size. The Pliensbachian increased size of austral Cylindrobullina species was considered by Ferrari and Hautmann (2022) to be related to a Pliensbachian cooling event (Korte et al, 2015); thus, largest specimens of Cylindrobullina (up to 30 mm) stem from the Pliensbachian of high paleolatitudes (south Patagonia) with inferred cold palaeotemperatures. Ferrari and Hautmann (2022) also suggested that the post extinction size increase of Cylindrobullina might have resulted from ecological (Gründel, 2010;Gründel and Nützel, 2012).…”
Section: Palaeobiogeographymentioning
confidence: 99%
“…This conclusion is supported by the phylogenetic analysis of Dinapoli and Klussmann-Kolb (2010), who indicated an occurrence of the Euthyneura stem line between the Middle Carboniferous and the Early Triassic and a first diversification of the clade between the Permian and the Triassic. The Early Mesozoic euthyneuran bubble snails in the extinct families Cylindrobullinidae and Tubiferidae are very similar in general shell morphology and ornamentation pattern to the extant Acteonidae and Ringiculoidea (see Kano et al, 2016;Ferrari and Hautmann, 2022). Thus, the common ancestor of Euthyneura might have had a thin, oval shell-shaped with a large body whorl, an elongated aperture and smooth surface with or without fine spiral cords, as is shown in early Mesozoic opisthobranchs (e.g., Cylindrobullina, Cossmannina, Conactaeon, Euconactaeon, Sinuarbullina).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation